Karakteristik Air yang Berisiko dengan Terjadinya Batu Saluran Kemih - Satriyo Dwi Suryantoro; Pradana Zaky; Faizal Kurniawan; Vetty Silvana Maulida (Universitas Faletehan, 2025)
Around 170,000 urinary tract stones (UTS) occur in Indonesia every year. The incidence rate of UTS is related to the source of drinking water. Recurrence of UTS can increase mortality and treatment costs. The purpose of this study was to find out the factors that cause urinary tract stones based on water characteristics. This type of research was analytical observational, using a multiple linear regression analysis design with a sample of 50 respondents selected using purposive sampling techniques. The characteristics studied using univariate analysis were water consumption characteristics, water sources, respondent health, water content, urine color, and urine composition. The regression analysis studied were the variables of PH, treatment, mineral water potable, taste water, well water source, soundness, tension, color, and clarity with the incidence of UTS. The results of the regression analysis showed that the p value (1.75) was greater than alpha so it can be concluded that there was no significant influence between PH, treatment, drinking mineral water, flavored water, well water source, soundness, tension, color, and clarity with the incidence of urinary tract stones.